Reexamining the Story of Islam and Nation States in Southeast Asia - Dadang Darmawan; Yohanes Slamet Purwadi (FOCUS, 2022)
This article will try to find out why Islam in Indonesia is able to unite various diverse ethnic groups in a unitary state without significant friction? While in Malaysia Islam gives spirit to Malay ethnicity to become the dominant element in all aspects of national and state life without being dragged into chauvinism? Why is it that Islam which is ethnical with certain ethnicities in the Philippines has become a serious deterrent to nationality in both countries? Three cases that together involved elements of Islam, ethnicity and nationalism but showed different manifestations of reaction. In each case Islam plays a different position and function, as a unifying Indonesia, the spirit of Malaysia and undermining the Philippines.